Choice of Optimal Asset Portfolio with and without Risk - Vásquez Serpa, Luis Javier (2018)
In this research we will present the "Choice of optimal portfolios of assets with and without risk", where we propose an efficient portfolio optimization model based on the theory of Markowitz (Assets with Risks), who won the Nobel Prize in Economics in 1990 for their contributions to the analysis of investment portfolios and corporate financing methods. Markowitz based on his theory, defines that for a given performance the risk that they have is minimal, this model is the most efficient when it comes to reducing risks. On the other hand, if we opt for an optimal risk-free portfolio, we will rely on the Sharpe Model to establish a pricing of financial assets, in which an investor can choose a risk exposure through a combination of income values fixed and a variable income portfolio.